2020
DOI: 10.1177/2332649220908608
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Feminisms: Disturbing Colonialism in Environmental Science Partnerships

Abstract: Efforts have been under way by Indigenous peoples to reanimate governance that includes people of all ages and genders. Simultaneous initiatives to decolonize science within environmental fields must confront how settler colonial systems can continue to operate under the guise of partnership. Indigenous feminist theories aid understanding of ongoing colonialism alongside heteropatriarchy and racism with attempts to dismantle oppression in everyday practice. The author examines governance in a North American en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…We hope that this article demonstrates ways in which research teams should be attentive to labor in designing a feminist political ecology team, and to recognizing power and privilege in praxis. Moreover, we recognize more work is needed in feminist political ecology -not only to address power, but specifically to attend to settler-scholar logics (Dhillon 2020).…”
Section: Research Design and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…We hope that this article demonstrates ways in which research teams should be attentive to labor in designing a feminist political ecology team, and to recognizing power and privilege in praxis. Moreover, we recognize more work is needed in feminist political ecology -not only to address power, but specifically to attend to settler-scholar logics (Dhillon 2020).…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…In our call to revisit integrating feminist methodologies in team-based FPE, we suggest that feminist political ecologists should continue to recognize epistemic and ontological norms of knowledge production within research teams and in their home institutional contexts -this is also a central concern for decolonizing methodologies (Dhillon 2020;Todd 2016;Tuhiwai Smith 2013). FPE can demonstrate the integration of insights from feminist scholars in studies of power (Ahlborg and Nightingale 2018: 383;Nightingale and Rankin 2014;Rocheleau 2008).…”
Section: Third Phasementioning
confidence: 99%
“…This perspective is consistent with the findings of social network analysis of gender relations in Indigenous-settler climate partnerships. Dhillon (2020) found that Indigenous women and youth were not well incorporated into the governance structures of a climate science boundary organization where decision-making roles were dominated by Indigenous men and white women.…”
Section: Relational and Structural Tensions In Environmental Boundary...mentioning
confidence: 99%
“…In particular, Native American women experienced intersectional inequalities even in partnerships that aimed to do otherwise (cf. Dhillon, 2020). Network members also regularly work through layers of insider/outsider dynamics (Jacob, 2006;Smith, 1999Smith, /2012.…”
Section: Recap and Conclusionmentioning
confidence: 99%
“…But decolonial FPE is more historical and spatial in its accounting for colonialities that exist to this day and are reproduced in academic scholarship and collective action (cf. Dhillon, 2020).…”
Section: Introductionmentioning
confidence: 99%